The deviant syntax of headlinese and its role in the pragmatics of headlines - Florent MONCOMBLE (E-REA)
The syntax of newspaper headlines in English displays features which, on a superficial level, set it apart from the norm of Standard English. This, however, is not to say that headlinese stands outside the notion of a linguistic norm: drawing from a corpus of various headlines, and looking at the specific fields of determiners and verb tenses, this article explores how the English of newspaper headlines constitutes a norm in itself which actually builds on the very potentialities of Standard English. Such an extension of the syntactic possibilities of English is designed to fit the pragmatic purpose of headlines, i.e. heighten the relevance of the newspaper article to the reader.